2014
DOI: 10.1089/zeb.2013.0923
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Paraquat Alters Behavioral Parameters and Dopamine Levels in Adult Zebrafish (Danio Rerio)

Abstract: Chronic exposure to paraquat (Pq), a toxic herbicide, can result in Parkinsonian symptoms. This study evaluated the effect of the systemic administration of Pq on locomotion, learning and memory, social interaction, tyrosine hydroxylase (TH) expression, dopamine and 3,4-dihydroxyphenylacetic acid (DOPAC) levels, and dopamine transporter (DAT) gene expression in zebrafish. Adult zebrafish received an i.p. injection of either 10 mg/kg (Pq10) or 20 mg/kg (Pq20) of Pq every 3 days for a total of six injections. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 98 publications
3
39
1
Order By: Relevance
“…The study of the consequences of pollutants exposures on behaviour has recently increased, especially for fish, in parallel to the expansion of the use of behaviour as an efficient indicator for neurotoxicity in pharmacology, toxicology, and ecotoxicology. With respect to this, we and others have shown that the exposure of fishes to pollutants using environmentally relevant exposure conditions can induce behavioural disruptions at various developmental stages (e.g., [9,10,11,12,13,14,15,16,17,18]). Other studies have shown that exposure to pollutants could modify monoamine neurotransmitter concentrations (e.g., [19,20,21,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the consequences of pollutants exposures on behaviour has recently increased, especially for fish, in parallel to the expansion of the use of behaviour as an efficient indicator for neurotoxicity in pharmacology, toxicology, and ecotoxicology. With respect to this, we and others have shown that the exposure of fishes to pollutants using environmentally relevant exposure conditions can induce behavioural disruptions at various developmental stages (e.g., [9,10,11,12,13,14,15,16,17,18]). Other studies have shown that exposure to pollutants could modify monoamine neurotransmitter concentrations (e.g., [19,20,21,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…They have high fecundity and short lifespans, which make them ideal for genetic study. Paraquat-treated zebrafish exhibited motor-related behavioral defects and reduced DAT expression, whereas nonmotor behaviors, such as social interaction and anxiety challenges, were unaltered [146]. For example, motor movements involving the basal ganglia in mammals are present in zebra fish telencephalon, and TH-positive neurons are present that resemble anatomical comparisons to the striatum [141].…”
Section: Alternative Modelsmentioning
confidence: 99%
“…This is particularly evident in zebrafish studies, where some have outlined a severe neurodegenerative impact of paraquat on dopamine and serotonin protein levels [25,26], while others observed no obvious phenotypes [10]. This variable effect extends to behavioral symptoms following treatment, where some groups observed significant motor impairment [27], while others report no fluctuations in any swimming activity parameter [10]. These results may be the consequence of varying treatment regimens.…”
Section: Introductionmentioning
confidence: 98%